The use of animation tools in the media space of the “Library Night” for the development of master’s students’ teamwork skills - Ekaterina A. Mamaeva; Dmitry N. Gribkov; Vladimir V. Matveev; Tatyana V. Masharova (RUDN Journal of Informatization in Education)
Problem statement . The modernization of library education involves the ability to use information tools, in particular computer animation, in working on projects. The maturity of teamwork skills largely determines the professional self-realization of multifunctional librarianship specialists. The study aimed at substantiating the effectiveness of using animation tools in the media space of the “Library Night” event to develop the teamwork skills of master’s students. Methodology . Theoretical and methodological analysis and generalization are used to determine the content and problems of developing teamwork skills in library and information education, and the inclusion of animation tools in the implementation of media projects. The Renderforest platform is used to develop didactic animation. The study involved 68 undergraduates from the Orel State Institute of Culture. The study of animation tools and their use for designing the media space of the library is implemented within the framework of classes in the discipline “Information Technologies in Science and Education”. The authors use V. Stefanson's methodology to assess the level of teamwork skills of master's students. With its help, the levels of their development, interconnected with personality qualities, are determined. For statistical processing, Pearson's chi-square test and Fisher's method (angular transformation) were used. Results . The ideas of a methodological approach are formulated, reflecting the necessary changes in the system of training specialists in library science, taking into account the digitalization of library and information services. The didactic potential of animation tools for improving the quality of library education, and, in particular, for developing the teamwork skills of undergraduates has been clarified: developing the ability to listen to the alternative opinions of other team members, accept the standards and values of the group, and follow the social and moral-ethical norms of the team. Statistically significant differences in the qualitative changes that occurred in the didactic system were determined. Conclusion . The use of animation tools in the media space of the “Library Night” event contributes to the development of teamwork skills among master’s students: new opportunities for collaboration and project activities, innovative work experience, etc. However, some factors complicate the process of team building in the media space of libraries: the lack of clear leadership in the library, the lack of communication between employees, the weak motivation, and low social status of the profession.